Fatigue behaviour of square-to-square hollow section T-joints with corner cracks - Ji, Hongli (2010)
In this study, the fatigue behaviour of the square-to-square hollow section (SSHS) T-joints with corner cracks is investigated. Both experimental work and numerical modelling and analysis are carried out. Crack profiles in SSHS joints subjected to fatigue loads are studied. A general equation for crack surface in SSHS joints is proposed and a fatigue life prediction procedure is introduced.